COVID-19 AND ITS FIRST WAVE: A RETROSPECTIVE ANALYSIS OF EARLY CASES IN A BORDER CITY OF BRAZIL - Barbosa Costa , Welisson; Chagas de Assis, Samuel; Gurgel do Carmo , Natalia; Dias Mendoza, Arthur; dos Santos da Silva, Rafael; Zarpelon, Luis Fernando; Terencio, Maria Leandra (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2023)
In this retrospective, single-center study, we included all the cases of the first wave of nCoV 2019 at Hospital Padre Germano Lauck, Foz do Iguaçu - PR, Brazil, from April to July 2020, confirmed by real-time RT-PCR and analyzed epidemiologic and clinical features. We aim to retrospectively describe and analyze the clinical and epidemiological characteristics of the cases in the first wave of COVID-19 in the city of Foz do Iguaçu, in Brazil. Categorical data are described by frequency and proportions, while numerical data were described by standard deviation (SD) and median interquartile range (IQR). The mean age of patients was 39 years, including 415 men (44%) and 535 women (56%). The prevalent comorbidities were diabetes, hypertension, and cardiovascular disease. Cough, headache, and myalgia were the common symptoms associated with COVID-19. Age was the main risk factor for death, as was Hypertension and Diabetes. This study found that the first wave of COVID-19 in Foz do Iguaçu had similar characteristics as studies conducted during the same epidemiological period. When compared to later analyses of different strains of the COVID-19 virus, it was seen that there was a predominance of different symptoms and ages of severe cases among infections caused by the Ômicron and Delta variants.